2016
DOI: 10.1002/14651858.cd012249
|View full text |Cite
|
Sign up to set email alerts
|

School-based interventions for improving contraceptive use in adolescents

Abstract: Since most trials addressed preventing STI/HIV and pregnancy, they emphasized condom use. However, several studies covered a range of contraceptive methods. The overall quality of evidence was low. Main reasons for downgrading the evidence were having limited information on intervention fidelity, analyzing a subsample rather than all those randomized, and having high losses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
88
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(92 citation statements)
references
References 90 publications
1
88
0
3
Order By: Relevance
“…The behaviors that distinguished the two lower risk clusters from the two higher ones—age at sexual initiation, birth control use at first intercourse and birth control use in the past year—are amenable to intervention . Adolescents’ exposure to comprehensive school‐based sexual education programs has been shown to be correlated with increased use of condoms and other contraceptives . Augmenting such programs with modules designed to increase adolescents’ awareness of how negative internalized emotions (e.g., poor body image, low self‐esteem) may compromise one's ability to negotiate safer sexual behavior might help reduce sexual risk behaviors among women who perceive themselves to be overweight.…”
Section: Discussionmentioning
confidence: 99%
“…The behaviors that distinguished the two lower risk clusters from the two higher ones—age at sexual initiation, birth control use at first intercourse and birth control use in the past year—are amenable to intervention . Adolescents’ exposure to comprehensive school‐based sexual education programs has been shown to be correlated with increased use of condoms and other contraceptives . Augmenting such programs with modules designed to increase adolescents’ awareness of how negative internalized emotions (e.g., poor body image, low self‐esteem) may compromise one's ability to negotiate safer sexual behavior might help reduce sexual risk behaviors among women who perceive themselves to be overweight.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a large number of systematic reviews that evaluated the effectiveness of these programmes (Chin 2012; Dick 2006; DiClemente 2008; Flisher 2008; Gallant 2004; Harrison 2010; Johnson 2003; Johnson, 2011; Kim 2008; Kirby 2007; Lazarus 2010; Magnussen 2004; Medley 2009; Michielsen 2010; Paul 2008; Shepherd 2010; Yankah 2008), including reviews that have focused solely on school-based interventions (Bennet 2005; Fonner 2014; Kirby 2006; Lopez 2016; Paul 2008), and a review of reviews (Mavedzenge 2013). Many of these reviews have suggested that school- and community-based prevention programmes for adolescents have been effective in delaying self-reported sexual activity, HIV-related preventative behaviours, adolescent pregnancy, and STIs (Chin 2012; Fonner 2014; Johnson 2003; Johnson, 2011; Kirby 2009; Laud 2016), although others have reported less, or mixed, success (Bennet 2005; DiCenso 2002; Lopez 2016 Oringanje 2016). The logic model for how these programmes might be thought to influence sexual and reproductive health outcomes can be seen in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Further, we conducted a separate review on interventions to improve access to health services for children under five in LMIC . Several previous reviews have explored evidence for interventions to address specific health needs for adolescents (aged 10–19 years) such as preventing unintended pregnancies , increasing physical activity , prevention of HIV , smoking cessation and improving contraceptive use . Whilst most previous reviews have focussed on individual health outcomes related to specific health needs, few reviews have focussed on outcomes related to health service access for older children in LMIC.…”
Section: Introductionmentioning
confidence: 99%